Burning mouth syndrome and saliva: detection of salivary trace elements and cytokines - NAMDAR PEKİNER, FİLİZ MEDİHA (WILEY, 2009)
Burning mouth syndrome (BMS) is considered a syndrome with an unknown cause. Roles of various trace elements and cytokines in saliva have been implicated in the development of BMS. The aim of the present study was to compare the levels of salivary trace elements [magnesium (Mg), zinc (Zn), copper (Cu)] and interleukin (IL)-2 and IL-6, and to search for a correlation between depression/anxiety and salivary trace elements and cytokines in BMS patients and controls. Thirty patients with BMS and 30 matched healthy controls participated in the study. Unstimulated saliva was collected from participants and salivary flow rates were determined. Mg, Zn and Cu levels were determined by atomic absorbance spectrophotometry. Cytokine immunoassay kits were used to determine the concentration of IL-2 and IL-6 in the whole saliva samples. Anxiety and depression were analyzed by means of the Speilberger State-Trait Anxiety Inventory (SAI-TAI) and Zung Self-Rating Depression Scale. Although subjects in the control group had significantly higher mean levels for Mg compared with BMS patients (P < 0.01), no statistically significant differences were observed in relation to Zn and Cu levels between the two groups (P < 0.001). There were no statistically significant differences in IL-2 and IL-6 levels of BMS and control groups, but subjects in BMS group had slightly, not significantly, higher mean levels for IL-6 compared with controls. Subjects in BMS group had significantly higher mean values for TAI compared with controls (P < 0.05). There were no statistically significant differences in relation to salivary levels of Mg, Zn, Cu, IL-2, IL-6 and depression/anxiety between BMS and control groups. The results of our study indicate that Mg levels could have an impact on symptoms of BMS and further studies are necessary to determine the importance of cytokines in the pathogenesis of BMS.
Keywords: anxiety; burning mouth syndrome; cytokines; magnesium; saliva; trace elements; MAJOR DEPRESSION; FLOW-RATE; MAGNESIUM; PAIN; INTERLEUKIN-6; GLOSSODYNIA; ASSOCIATION; DIAGNOSIS; SYMPTOMS; ILLNESS